Paul Davidson's Economics - Richard P. F. Holt; J. Barkley Rosser; L. Randall Wray (Levy Economics Institute of Bard College, 1998)
Paul Davidson is one of the best known and most influential Post Keynesian economists. He has insisted throughout his career that economists should focus on real world problems and that the purpose of economic policy is to help society become more humane and civilized. He is also known for his insistence on adhering to the words and ideas of John Maynard Keynes. This article reviews his contributions to monetary theory, international economics, aggregate supply theory, and environmental economics.
Keywords: 330